A Report of Two Patients with Food Protein-induced Enterocolitis Mimicking Bartter Syndrome - Sepideh Darougar; Arezoo Shirzani; Mahboubeh Mansouri; Masoumeh Mohkam (Iranian Journal of Allergy, Asthma and Immunology, 2021)
Food protein-induced enterocolitis syndrome (FPIES), is a non-IgE mediated food allergy presenting in infants younger than 12 months. Diagnostic delay may occur due to overlapping clinical symptoms with several conditions. Here, we present two cases of FPIES, mistakenly diagnosed and treated as Bartter syndrome. This study aims to emphasize the several features of this syndrome that may mimic other diagnoses and sometimes leading to near-death events due to delay in the diagnosis and improper treatment. The first patient was a 30-month-old boy with multiple episodes of profuse vomiting and diarrhea within 1 hour after breastfeeding, beginning from the first month of life progressing to hypokalemia and metabolic alkalosis at the age of 5 months leading to the diagnosis of Bartter syndrome. The second patient had a history of unremitting diarrhea which had been started soon after his first breastfeeding followed by biliary vomiting on the 7th day of life. He was treated in another hospital for neonatal sepsis, however, without an appropriate response to treatment. To conclude, despite the current belief on the rarity of FPIES, it is a more prevalent disease than expected with various non-specific manifestations imitating other conditions which may result in diagnostic delay and sometimes fatalities. To shed light on the importance of the physicians’ awareness of this syndrome, these two cases are presented here as examples of FPIES imitating other disorders.